Penataan dan Inventarisasi Tanaman Obat di UPTD Puskesmas III Dinas Kesehatan Kecamatan Denpasar Selatan - Setyawan Guna Dharma; Ayu Nilam Tresna Dewi; Anak Agung Ketut Sri Trisna Dewi Widhiani; Nyoman Eva Sri Wahyuni; I Gusti Agung Sri Astuti; Putu Judy Satyawati Sudarmo; I Gusti Agung Ayu Kartika (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Puskesmas as a health facility that is easily accessible to the community, of course, is a forum in promoting, especially introducing family medicinal plants (TOGA) that have been used for generations as an alternative treatment. Public understanding related to Family Medicinal Plants (TOGA) through the health center is still very minimal, therefore this community service is carried out on the basis of these problems through structuring and inventorying plants with medicinal properties at the UPTD Puskesmas III Health Office of the South Denpasar District Health Office. This community service team consists of 3 people, namely 1 lecturer and 2 students. The method used in this service includes 3 stages, namely: the preparation stage, starting with the submission of applications and discussions regarding the schedule and accompanied by conducting a survey of the location of the toga planting. Furthermore, the implementation stage begins with the cleaning of the planting area, planting new types of medicinal plants, plant care, making toga nameplates, and ending with the submission and installation of toga nameplates. there are 49 nameplates of medicinal plants along with scientific names and efficacy installed. The last stage is the preparation of a report that contains details about this community service activity.